Donald Benham Civil War collection - Benham, Donald
Correspondence, speeches, military orders and records, financial and legal records, and other papers of Union Army officers and soldiers concerning recruitment, enlistment, camp life, battle engagements, military strategy, and distribution of military supplies. Other subjects include diplomatic policy, abolition and slavery, and social conditions in the South during its occupation by Union forces. Includes records of the U.S. Navy Potomac Flotilla pertaining to communications in the Chesapeake Bay and the Potomac River region; correspondence of Horace Greeley concerning Abraham Lincoln, prosecution of the war, and political battles in Washington, D.C.; an eyewitness account of Robert E. Lee's evacuation of Petersburg and Richmond, Virginia, and his subsequent retreat westward; and a speech by William Woods Averell concerning his life and military career relating, in part, to wartime espionage and spy networks in Washington, D.C., following the First Battle of Bull Run.
Collector.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Averell, William Woods, -- 1832-1900.; Greeley, Horace, -- 1811-1872 -- Correspondence; Lee, Robert E. -- 1807-1870.; Lincoln, Abraham, -- 1809-1865.; United States. -- Army -- Military life; United States. -- Army -- Recruiting, enlistment, etc; United States. -- Army -- Supplies and stores; United States. -- Navy. -- Potomac Flotilla; Bull Run, 1st Battle of, Va., 1861.; Slavery -- United States; Strategy -- History -- 19th century; Chesapeake Bay (Md. and Va.) -- History -- Civil War, 1861-1865.; Confederate States of America -- Social conditions; Maryland -- History -- Civil War, 1861-1865.; Petersburg (Va.) -- History -- Civil War, 1861-1865.; Potomac River -- History -- Civil War, 1861-1865.; Richmond (Va.) -- History -- Civil War, 1861-1865.; United States -- Foreign relations -- 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Secret service; United States -- Politics and government -- 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Collectors